Life History, Growth, and Reproductive Biology of Four Mobulid Species in the Bohol Sea, Philippines - Rambahiniarison, Joshua M.; Lamoste, Mary Jane; Rohner, Christoph A.; Murray, Ryan; Snow, Sally; Labaja, Jessica; Araujo, Gonzalo; Ponzo, Alessandro (Frontiers in Marine Science, 2018)
In light of the global decline of mobulid populations and the necessity for sustainable fisheries management, baseline data for population dynamics were collected from a targeted fishery in the Bohol Sea, Philippines. This study focused on life-history parameters and reproductive cycles of four mobulid rays (Mobula thurstoni, M. japanica, M. tarapacana, and Manta birostris), and re-estimated their intrinsic population growth rates. Size and reproductive data were collected from 1,509 specimens (30% of catch) landed in two fishing seasons in 2015 and 2016. Size-at-birth was reviewed, and analysis of the embryos and follicles did not show any clear seasonality in the reproductive cycle, but supported an interbreeding interval. Females of all species matured at a larger size than males, and exhibited a larger size-at-pregnancy than -at-maturity. This delay in reproduction resulted in population growth rates lower than the actual rmax when based on size-at-pregnancy (rmat=rmax=0.016-0.055 year-1 and rpreg=0.008-0.044 year-1), and a population doubling time of 15.8-86.6 years. This study suggests that population growth rates previously reported were overestimated. In light of the Convention on International Trades of Endangered Species (CITES) and Convention on Migratory Species (CMS) assessments, while fisheries management should reflect the delayed maturation of these species and the slower population growth potential, at the current status of these population, the sustainability of any exploitation level seems unrealistic and strongly discouraged.